2018
DOI: 10.1371/journal.pone.0193572
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Neisseria meningitidis W:cc11 invasive disease in Chile has no correlation with carriage in adolescents

Abstract: Neisseria meningitidis is a human exclusive pathogen that can lead to invasive meningococcal disease or may be carried in the upper respiratory tract without symptoms. The relationship between carriage and disease remains poorly understood but it is widely accepted that decreasing carriage by immunization should lead to a reduction of invasive cases. Latin America has experienced an increased incidence of serogroup W invasive cases of Neisseria meningitidis in the last decade. Specifically in Chile, despite lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
2
15
1
Order By: Relevance
“…No statistically significant differences were seen between carriers and noncarriers in univariate analysis. Unlike the findings by Rubilar and colleagues [40], none of the MenW carriage isolates were attributed to cc11 [41].…”
Section: Chilecontrasting
confidence: 77%
See 3 more Smart Citations
“…No statistically significant differences were seen between carriers and noncarriers in univariate analysis. Unlike the findings by Rubilar and colleagues [40], none of the MenW carriage isolates were attributed to cc11 [41].…”
Section: Chilecontrasting
confidence: 77%
“…Interestingly, studies from Chile found a high rate of MenW cc11 among disease isolates, with only a very small percentage, if any, of carriage isolates attributed to cc11 [40,41]. The authors hypothesized that the low carriage of MenW cc11 in Chile could be attributed to enhanced virulence of this strain, allowing most infections to result in disease rather than carriage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three cases were described in Chile (2013) in which MenW IMD presented as a primary respiratory tract infection; rapid clinical deterioration with an intense systemic inflammatory response soon followed [32]. All of Chile's MenW IMD cases in 2013 were caused by ST-11 [33]. At early stages, meningococcal disease usually presents as cold-like symptoms, including sore throat, cough, coryza and otalgia [2].…”
Section: Pneumonia and Upper Respiratory Tract Infectionsmentioning
confidence: 99%